A study exploring the impact of Chinese university performance appraisal on university teachers' academic innovation behaviour - Shi, Haochen (2020)
The development of university teacher performance appraisal in China is later than that of European and American countries, so the existing university teacher performance appraisal in China is not mature. In addition, academic misconduct in academic innovation has appeared in China in recent years. Therefore, universities need to explore effective and reasonable methods to promote academic innovation of university teachers. Based on the self-determination theory, this paper takes teachers from certain universities in China as the research sample and collects data through questionnaires to explore the impact of university performance appraisal on teachers' academic innovation behaviour and motivation. The research results reveal the relationship between performance appraisal, innovation motivation and innovation behaviour.